2023
DOI: 10.1021/acsnano.3c06395
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Free-Energy Shapes of Ag Nanocrystals: Vacuum vs Solution

Tianyu Yan,
Huaizhong Zhang,
Kristen A. Fichthorn

Abstract: We use two variants of replica-exchange molecular dynamics (MD) simulations, parallel tempering MD and partial replica exchange MD, to probe the minimum free-energy shapes of Ag nanocrystals containing 100−200 atoms in a vacuum, ethylene glycol (EG) solvent, and EG solvent with a PVP polymer containing 100 repeat units. Our simulations reveal a shape intermediate between a Dh and an Ih, a Dh-Ih, that has distinct structural signatures and magic sizes. We find several prominent features associated with entropy:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…116 is not a magic size for the Ih and the surface atoms of this nanocrystal are distorted from those in a perfect Ih – thus, we designate it as a “twisted Ih”. We note that 116 is a magic size for the Dh–Ih 39 and the “twisted Ih” bears similarity to the Dh–Ih in its surface atoms. Previously unclassified atoms with CNA are shown in yellow in Fig.…”
Section: Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…116 is not a magic size for the Ih and the surface atoms of this nanocrystal are distorted from those in a perfect Ih – thus, we designate it as a “twisted Ih”. We note that 116 is a magic size for the Dh–Ih 39 and the “twisted Ih” bears similarity to the Dh–Ih in its surface atoms. Previously unclassified atoms with CNA are shown in yellow in Fig.…”
Section: Methodsmentioning
confidence: 80%
“…Interestingly for Ag, we observed that SCSF structures had a lower free energy (more frequent occurrence) than FCC structures – at sizes where such shapes occurred. 39 We attributed the preference for SCSF to the low stacking-fault energy for Ag, 53 which complements the high configurational entropy associated with stacking faults to produce a majority of SCSF shapes. Cu has a higher stacking-fault energy than Ag 53 and though the most probable structures for the FCC and SCSF are close in energy (see Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations